Environmental enrichment and welfare in animal production - Ricci, Gisele Dela; Titto, Cristiane Gonçalves; de Sousa, Rafael Teixeira (Revista de Ciências Agroveterinárias, 2017)
Animal welfare is among the main demands of consumers, who are increasingly critical of the quality of life within the environment, which requires the use of static conducts in systems for animal production. From this perspective, the objective of this study was to describe the importance of environmental enrichment in promoting improved welfare in animal production. Environmental enrichment has as main characteristic to reduce stimuli that generate stressful responses and allow the presentation of natural behavior, avoiding the appearance of stereotyped behaviors in confined animals. Natural behavior was defined as the one in which the animal tends to perform freely, by bringing pleasure or promoting good physiological functioning. While animal welfare is related to housing conditions such as bioclimatology and plant biophysics, it can be measured from physiological and behavioral assessments. Stress is seen as a set of intense and prolonged physiological reactions that result in imbalance of homeostasis, with important and irreversible effects on the animals. Thus, it is concluded that the use of environmental enrichment can greatly contribute to the reduction of stressors, improving animal welfare in production systems.